Polar stratospheric clouds initiated by mountain waves in a global chemistry–climate model: a missing piece in fully modelling polar stratospheric ozone depletion - Orr, Andrew; Hosking, J. Scott; Delon, Aymeric; Hoffmann, Lars; Spang, Reinhold; Moffat-Griffin, Tracy; Keeble, James; Abraham, Nathan Luke; Braesicke, Peter (Atmospheric Chemistry and Physics, 2020)
An important source of polar stratospheric clouds (PSCs), which play a crucial role in controlling polar stratospheric ozone depletion, is the temperature fluctuations induced by mountain waves. These enable stratospheric temperatures to fall below the threshold value for PSC formation in regions of negative temperature perturbations or cooling phases induced by the waves even if the synoptic-scale temperatures are too high. However, this formation mechanism is usually missing in global chemistry–climate models because these temperature fluctuations are neither resolved nor parameterised. Here, we investigate in detail the episodic and localised wintertime stratospheric cooling events produced over the Antarctic Peninsula by a parameterisation of mountain-wave-induced temperature fluctuations inserted into a 30-year run of the global chemistry–climate configuration of the UM-UKCA (Unified Model – United Kingdom Chemistry and Aerosol) model. Comparison of the probability distribution of the parameterised cooling phases with those derived from climatologies of satellite-derived AIRS brightness temperature measurements and high-resolution radiosonde temperature soundings from Rothera Research Station on the Antarctic Peninsula shows that they broadly agree with the AIRS observations and agree well with the radiosonde observations, particularly in both cases for the “cold tails” of the distributions. It is further shown that adding the parameterised cooling phase to the resolved and synoptic-scale temperatures in the UM-UKCA model results in a considerable increase in the number of instances when minimum temperatures fall below the formation temperature for PSCs made from ice water during late austral autumn and early austral winter and early austral spring, and without the additional cooling phase the temperature rarely falls below the ice frost point temperature above the Antarctic Peninsula in the model. Similarly, it was found that the formation potential for PSCs made from ice water was many times larger if the additional cooling is included. For PSCs made from nitric acid trihydrate (NAT) particles it was only during October that the additional cooling is required for temperatures to fall below the NAT formation temperature threshold (despite more NAT PSCs occurring during other months). The additional cooling phases also resulted in an increase in the surface area density of NAT particles throughout the winter and early spring, which is important for chlorine activation. The parameterisation scheme was finally shown to make substantial differences to the distribution of total column ozone during October, resulting from a shift in the position of the polar vortex.